CONSTRUCTING PEACE AS RESISTANCE: A CRITICAL DISCOURSE ANALYSIS OF INDONESIAN FOREIGN POLICY IN THE ISRAELI-PALESTINIAN CONFLICT - Rusyfa, Imamati Zikra Ar; Datang, Frans Asisi; Junaidi, Junaidi (Journal of Pragmatics and Discourse Research, 2026)
The concept of peace remains contested, particularly in the Israeli-Palestinian conflict, where it is framed either as national security or as justice and self-determination. This study investigates how Indonesian Presiden Prabowo Subianto discursively constructs the idea of peace in 2024 inauguration speech, reflecting Indonesia’s long-standing commitment to anti-colonialism and Palestinian independence. Using a transdisciplinary critical discourse analysis that integrates systemic functional linguistics (SFL) and argumentation theory, the research identifies how values, goals, circumstances, means-goals, and claims are articulated linguistically to legitimize Indonesian’s foreign policy stance. The findings show that peace is framed through anti-colonial values, the pursuit of Palestinian sovereignty, recognition of ongoing humanitarian crisis, and the principle of “free and active” foreign policy. Prabowo employs relational and material process, inclusive pronouns, and high modality language to construct solidarity as both a moral leader of the Global South. These challenging dominant global narratives equate peace with security while ignoring structural injustices. While the study demonstrates the role of political speeches in shaping collective moral visions, its reliance on a single speech limits the scope and generalizability of the analysis. Future research should expand to include comparative discourse from multiple leaders and contexts, as well as media framing, to better understand how peace is discursively negotiated across geopolitical landscapes.